The Hungarian tax regulation on the land and agricultural activity - Nagy, Zoltán (Zbornik radova Pravnog fakulteta u Novom Sadu, 2018)
This study examines the Hungarian tax law regulations regarding agricultural activities and the tax law status of arable land. The examination focuses on three tax categories since the scope of this study does not make it possible to perform a thorough examination of all the tax categories as well as these three tax categories focus the most on the special status of arable lands and food production. The three tax categories - Personal Income Tax, Value Added Tax and Levy – depict the sector’s tax law specialties. The most significant regulations can be found on the field of Personal Income Tax since rhis tax category offers possibilities to diversely regulate the agricultural activities. The Value Added Tax and Levy mostly helps the agricultural activities with special regulations, tax exemptions and tax benefits.